2018
DOI: 10.1101/502823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

p62-mediated Selective Autophagy Endows Virus-transformed Cells with Insusceptibility to DNA Damage under Oxidative Stress

Abstract: 1DNA damage response (DDR) and selective autophagy both can be activated by reactive 2 oxygen/nitrogen species (ROS/RNS), and both are of paramount importance in cancer 3 development. The selective autophagy receptor and ubiquitin (Ub) sensor p62 plays a key role in 4 their crosstalk. ROS production has been well documented in latent infection of oncogenic viruses 5 including Epstein-Barr Virus (EBV). However, p62-mediated selective autophagy and its interplay 6 with DDR have not been investigated in these set… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Taken together, our data and that of others support that viral KSHV enhancement of autophagy is central to latent viral tumourigenesis and the creation of a proinflammatory environment and may also play an important role in regulating the balance between latent versus lytic gene expression for KSHV and related herpesviruses (Dong et al , 2016; Park et al , 2016; Wang et al , 2019). Although this may suggest that targeting autophagic processes could be a useful strategy for treating KS, as supported by the regression of iatrogenic KS lesions after treatment with the mTORC1 complex inhibitor and autophagy inducer, rapamycin (Stallone et al , 2005), the complicated balance of autophagy regulation by KSHV suggests the need for more selective therapies.…”
Section: Discussionsupporting
confidence: 83%
“…Taken together, our data and that of others support that viral KSHV enhancement of autophagy is central to latent viral tumourigenesis and the creation of a proinflammatory environment and may also play an important role in regulating the balance between latent versus lytic gene expression for KSHV and related herpesviruses (Dong et al , 2016; Park et al , 2016; Wang et al , 2019). Although this may suggest that targeting autophagic processes could be a useful strategy for treating KS, as supported by the regression of iatrogenic KS lesions after treatment with the mTORC1 complex inhibitor and autophagy inducer, rapamycin (Stallone et al , 2005), the complicated balance of autophagy regulation by KSHV suggests the need for more selective therapies.…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, recent studies have indicated that oncogenic viruses induce p62 expression in their latency, through different mechanisms, including the Keap1-NRF2 pathway [40,41]. We have shown that EBV and HTLV1 activate p62mediate selective autophagy in their latency [42]. To further explore the mechanisms, we have accumulated evidence showing that EBV and HTLV1 induce p62, partially by NFκB that is activated downstream of LMP1 and Tax signaling pathways, respectively, and also likely by the Keap1-NRF2 pathway (to be published).…”
Section: Ros Activate Various Transcription Factors Such Asmentioning
confidence: 71%
“…We have shown that a well-controlled autophagy-p62 interplay renders EBV-infected cells with the ability to balance pro-survival DNA damage resistance and pro-mutagenic genomic perturbation under oxidative stress [42,53], and have defined two distinct roles for the autophagy-p62 interplay in this setting: cytoplasmic p62 mediates selective autophagy, and nuclear p62 upon autophagy inhibition represses DNA repair at least by promoting proteasomemediated degradation of CHK1 and RAD51 [42]. These original findings disclose novel mechanisms underneath LMP1-mediated oxidative DDR.…”
Section: P62-mediated Selective Autophagy Serves As An Alternative Dn...mentioning
confidence: 99%
“…Recently, an increasing number of studies have confirmed that under conditions of various intracellular or extracellular pressures, including nutrient deficiency, and endoplasmic reticulum, oxidative and metabolic stresses, such as hypoxia and high concentrations of insulin, SQSTM1/p62 may act as either a proto-oncogene or tumor suppressor gene, promoting or inhibiting malignant tumor progression, respectively (20)(21)(22)(23). By directly binding to numerous cancer-associated genes, such as Tribbles 3, EGFR, COX-2, MMP1/2, membrane type-MMP, c-Myc, Snail, Twist (20), RAD51 recombinase, filamin A (21), ring finger protein 168 (an E3 ubiquitin-protein ligase) (22) and checkpoint kinase 1 (23), SQSTM1/p62 can mitigate genetic instability and DNA damage foci, and induce DNA repair, thereby playing a role in cancer oncogenesis, malignant progression, senescence and chemoradiotherapeutic sensitivity (20)(21)(22)(23). Since SQSTM1/p62 is at the center of a hub of various complicated signaling pathways in different cancer types and as its functions have wide implications in different cellular systems, the underlying regulatory mechanisms of its role in steering tumor progression are not entirely known and remain to be revealed in the future.…”
Section: Introductionmentioning
confidence: 99%